The epidemiology of fatal cyclist crashes over a 14-year period in Alberta, Canada. (December 2015) - Gaudet, Lindsay; Romanow, Nicole; Nettel-Aguirre, Alberto; Voaklander, Donald; Hagel, Brent; Rowe, Brian
Abstract Background Cycling is a popular recreational activity and a common transportation option; however, cycling-related injuries can be fatal. There are few studies of cycling fatalities in Canada and none in a region as sparsely populated as Alberta. Methods A chart review was conducted of cyclists involved in fatal crashes. Charts for deaths that occurred between 1998 and 2011 (inclusive) were identified and abstracted onto standardized forms. Personal characteristics and crash circumstances, including motor vehicle involvement, were collected; mechanisms of fatally injured cyclists across age groups were compared. Census data were used to calculate region-specific and provincial age-specific cycling fatality rates. Results Charts from 101 deaths over 14 years were reviewed. Events mainly occurred during the summer. There were more fatalities in urban (64 [63 %]) than in rural settings. Collisions with motor vehicles and cyclist-only crashes accounted for 68 and 15 % of cycling fatalities, respectively. Most (87 %) deceased cyclists were male, and the median age was 47 years (inter-quartile range: 25, 58). The population-based fatality rate over the study period was highest among deceased cyclists older than 65. Helmet use was reported in 26 (26 %) cases and increased with age. Alcohol use was detected in 25 (25 %) cases. Conclusions Fatal cycling crashes in Alberta typically involve adults riding on urban roads and collisions with motor vehicles. While helmet legislation has reduced non-fatal cycling head injuries, deaths may be further prevented by physical separation of cyclists and motor vehicles and avoidance of substance use while operating bicycles.